2022
DOI: 10.1177/20417314221143059
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials delivery strategies to repair spinal cord injury by modulating macrophage phenotypes

Abstract: Spinal cord injury (SCI) causes tremendous harm to a patient’s physical, mental, and financial health. Moreover, recovery of SCI is affected by many factors, inflammation is one of the most important as it engulfs necrotic tissue and cells during the early stages of injury. However, excessive inflammation is not conducive to damage repair. Macrophages are classified into either blood-derived macrophages or resident microglia based on their origin, their effects on SCI being two-sided. Microglia first activate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…Then, the homogenate was placed on ice for 45 min to lyse the cells, and the total protein solution was concentrated through centrifugation at 13,523g for 20 min. The levels of IL-1β, IL-6, TNF-α, and TGF-β in the tumors were measured by ELISA kits. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the homogenate was placed on ice for 45 min to lyse the cells, and the total protein solution was concentrated through centrifugation at 13,523g for 20 min. The levels of IL-1β, IL-6, TNF-α, and TGF-β in the tumors were measured by ELISA kits. , …”
Section: Methodsmentioning
confidence: 99%
“…The levels of IL-1β, IL-6, TNF-α, and TGF-β in the tumors were measured by ELISA kits. 53,54 2.14. Statistical Analysis.…”
Section: Tumor Growth Inhibition and Immune Activation Assays In Vivomentioning
confidence: 99%
“…The survival rate and long-term survival of MSCs in hostile environments remain unresolved issues (144). Gels and scaffolds based on stem cell therapy can deliver MSCs to the site of injury and release MSCs slowly and continuously to the site of injury (145)(146)(147)(148)(149). Tissue engineering strategies can reduce the number of times that MSCs are administered to the patient and reduce the mechanical damage at the site of puncture.…”
Section: Challenges In the Clinical Application Of Msc Therapymentioning
confidence: 99%
“…[ 158 ] While several studies have demonstrated effective alteration of macrophage gene expression in the injured cord lesion site, the majority have used viral delivery with relatively few using nonviral strategies. Nevertheless, several biomaterial‐based strategies have proven capable of modifying macrophage phenotype [ 159 ] and nonviral delivery as a viable approach to alter macrophage activity and gene expression. For example, chitosan nanoparticles carrying miR‐124 (a mediator of microglia quiesence [ 160 ] ) injected into the injured rat spinal cord significantly reduced the number of ED‐1 positive macrophages in the injury site and were associated with reduced markers of inflammation.…”
Section: Nonviral Nanoparticle Delivery Of Transgenes To Different Ty...mentioning
confidence: 99%